Effect of Different Plant Covers on Soil Characteristics - Singh, Ravender; Singh, R. K.; Singh, Kalyan (Indian Forester, 1990)
Effect of different plant cavers on pbysico-chemical properties of soil was evaluated in Doon Valley environmental conditions. Amount of organic carbon, total nitrogen, available phosphorus and potash, exchangeable magnesium and cation exchange capacity was highest in soils under Eucalyptus hybrid plantations, and lowest in soils under agriculture landuse except the lowest values of available phospborus and potash in soils under Chir (Pinus roxburghii). Available nitrogen in agricultural soils and exchangeable calcium in soils under Teak (Teeona grandis) were highest in amount while these nutrients were lowest in soils under Sal (Shorea robusla) and agriculture, respectively. Other species exhibited different patterns of soil characteristics. The highest C:N ratio in soil. Under Subabul and lowest in soils under Chir iniicated bigbest production of decomposable leaf litter is oils under Subabul and lowest in soils under Chir. The surface soil (0-10 cm deep) contained bighest amount of mineral nutrients. Seasonally, mineralization of nutrients was found to be highest in the month of February and lowest in June.